The Livelihood Analysis in Merapi Prone Area After 2010 Eruption - Susy Nofrita; B.G.C.M. Bart Krol (Indonesian Journal of Geography, 2014)
As stated in Regent Regulation No. 20 Year 2011 about Merapi Volcano Disaster-Prone Area, Merapi eruption in 2010 affected larger area than before included Kalitengah Lor, Kalitengah Kidul and Srunen hamlet which was now categorized as prone area zone III or the most dangerous area related to Merapi volcano hazard and was forbidden to live at. But its local people agreed to oppose the regulation and this area had been 100% reoccupied. This research examined about the existing livelihood condition in Kalitengah Lor, Kalitengah Kidul and Srunen that had been changed and degraded after 2010 great eruption. The grounded based information found that 80% of households sample were at the middle level of welfare status, meanwhile the high and low were at 13% and 7% respectively. Each status represented different livelihood strategy in facing the life in prone area with no one considered the Merapi hazard, but more economic motivation and assets preservation. The diversity in strategy was found in diversification of livelihood resources which were dominated by sand mining, farming and dairy farming.